Majhudatu ِAl-Ustadz Dr. Abdullah Al-Tayeb fi Nasyr al-Lughah al-‘Arabiyyah: (Efforts of Professor Dr. Abdullah Al-Tayeb in Spreading the Arabic Language) - Haroun, Hajir Khamis (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2023)
God, the Blessed and Exalted, has honored the Arabic language with an honor that no other language has attained, when He, may He be glorified and exalted, sent down His Book, which is dear to the heart of His Messenger and Prophet Muhammad bin Abdullah, may God’s prayers and peace be upon him. Its value and gain from the elements of the ability to grow non-stop, which made it distinguished, so it became a human language and a global tongue since the advent of Islam, which made African governmental and private institutions exert their efforts in serving the Arabic language and supporting Arab educational institutions in Africa and abroad. The researcher chose Professor Dr. Abdullah Al-Tayyib because of his valuable efforts in spreading the Arabic language in Africa, especially Nigeria and other countries. Arab countries and Africa. Given the source of the data to be collected and used, this study uses library research (library research) and by looking at the data taken from the presented theory, this research is used qualitatively because the data used is not in the form of numbers. The method used to collect data in this study is the listening method, and its source is not only from listening to spoken language, but also from written language. The click technique is an attempt to obtain data by trying to intercept the use of someone's language and is the underlying technique in this method This study aims to shed light on the role of Arab educational institutions through the efforts of our esteemed scholars in Africa. The paper contains three axes, the first axis: introducing Dr. The second axis: his scientific writings and lectures. The third axis: the efforts of Professor Dr. Abdullah Al-Tayeb in spreading the Arabic language.